THE CORRELATION OF ADOLESCENT’S KNOWLEDGE AND ATTITUDE TO DRUGS WITH ADOLESCENT’S DRUG ABUSE BEHAVIOR IN THE COMMUNITY HEALTH CENTER OF KESUNEAN, CIREBON - Ayatullah Ouve Rahadiani Permana; Uswatun Khasanah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The reports on the number of drug abuse in Indonesia by the National Narcotic Agency (NNA) showed 3.3 million drug users in 2008 and 3.8 million drug users in 2014 in which its number keeps increasing year after year. The number of teenagers who become drug users in Cirebon is quite high, i.e. 25% compared to unemployed people of 19%, and followed by private employees and government employees of 56%. Data from community health center show that drug users who underwent treatment and were sent to rehabilitation center in 2017 were 32 people; it was higher than in 2016, i.e. 10 people. Adolescence is a transition period between childhood and adulthood. There are several factors influencing mental abilities, knowledge, and attitudes. It makes adolescents may consume narcotics, psychotropic abuse and other drug addictive substances. The community health center of Kesunean has an Integrated service post (ISP) program called REMPONG PISAN (an ISP who cares for HIV/AIDS and Narcotics) aiming to make adolescent understand about HIV/AIDS and drugs and to make them healthy. This ISP program is conducted once a month with one of the activities is education about HIV/AIDS and drugs. Aim: To observe the correlation of adolescent’s knowledge and attitudes to drugs with drug abuse behavior among adolescents at the ISP. Method: This research was an observational analytic study with a cross-sectional design. The sample was determined using consecutive sampling technique during the implementation of the ISP at the 2 neighborhood in the community health center of Kesunean. The data were analyzed using Pearson correlation to determine the correlation of adolescent’s knowledge and attitudes to drugs with drug abuse behavior among adolescents. Results: Statistical analysis shows that there was no significant correlation between knowledge and drug abuse behavior (p = 0.180 and; r = -0,201), there was no significant correlation between attitudes with drug abuse behavior (p = 0.264; r= -0,168), however, there was a significant correlation between knowledge and attitudes towards drug abuse (p = 0.000; r = 0,710**). Conclusion: The better the adolescent’s knowledge about drugs, the better their attitude will be. In this case, good teen behavior is influenced by good knowledge and attitude. Keywords: NNA, Drug, Knowledge, Attitude, Drug Abuse Behavior